2016
DOI: 10.1016/j.bjorl.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Setting of an endoscopic nasal reference point for surgical access to the anterior base through an anatomical study on cadavers

Abstract: The methodology defined the nasal point of reference, considering an absence of variation in the cadavers' characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…The consistency of the AB measurements evaluated in the dissection and tomography analyses confirms the hypothesis of a regular distance between the posterior wall of the maxillary sinus and the skull base observed in surgical practice and in two studies performed on cadavers 12 and CT scans, however with a difference of 0.5 cm between them. The new research with the same measurements on CT scans and on cadavers showed that they were > 1.5 cm in all cases evaluated.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The consistency of the AB measurements evaluated in the dissection and tomography analyses confirms the hypothesis of a regular distance between the posterior wall of the maxillary sinus and the skull base observed in surgical practice and in two studies performed on cadavers 12 and CT scans, however with a difference of 0.5 cm between them. The new research with the same measurements on CT scans and on cadavers showed that they were > 1.5 cm in all cases evaluated.…”
Section: Discussionsupporting
confidence: 82%
“…11 Knowing the anatomical references and fixed measurements with almost no variation in terms of gender, race, age, weight, and height might provide surgeons more reliability, minimizing complications and optimizing interventions in the nasal sinuses. 12 The hypothesis of a regular distance, greater than 1.5 cm, between the posterior wall of the maxillary sinus and the skull base has been presented in a research with 120 nasal cavities of cadavers. 12 The purpose of the present research was to measure and compare the distance from the posterior wall of the maxillary sinus to the anterior skull base in cadavers and on CT scans to determine a measurement as an anatomical reference in imaging exams to assist the surgeon in endoscopic nasal surgeries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of this area of the body is particularly important in the case of death due to sepsis or inflammation of unknown origin, so it cannot be omitted in the case of post-mortem diagnostics [ 69 , 70 ]. The cranial sinuses may also be subject to post-mortem endoscopic evaluation, which has an important diagnostic value in the case of drownings [ 71 , 72 ]. Moreover, penetration of the endoscope into the sinuses also allows for indirect assessment of damage to the skull base [ 71 ].…”
Section: Supplementary Proceduresmentioning
confidence: 99%
“…The cranial sinuses may also be subject to post-mortem endoscopic evaluation, which has an important diagnostic value in the case of drownings [ 71 , 72 ]. Moreover, penetration of the endoscope into the sinuses also allows for indirect assessment of damage to the skull base [ 71 ]. In cases where it is necessary, laparoscopic autopsy can be supplemented with endoscopic joint examination.…”
Section: Supplementary Proceduresmentioning
confidence: 99%